2012
DOI: 10.1007/s10811-011-9773-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Moringa oleifera seed flour as a flocculating agent for potential biodiesel producer microalgae

Abstract: Microalgal biofuel alternatives have been hindered by their cost and energy intensive production. In the microalgal harvesting process, the intermediate step of flocculation shows potential in drastically reducing the need for costly centrifugation processes. Moringa oleifera seeds, which have been used for water treatment due to their high flocculation potential, low cost and low toxicity, are presented in this paper as strong candidate for flocculating Chlorella vulgaris, a microalgae with high biodiesel pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(49 citation statements)
references
References 34 publications
(51 reference statements)
2
43
1
3
Order By: Relevance
“…The coagulation-flocculation process, followed by sedimentation, has been the most widely adopted method because it has been shown to be economically viable for large production volumes of biomass 11,12 . The coagulation-flocculation process can promote microalgal aggregation by the addition of coagulants (electrolytes), which can be metal salts, natural or synthetic polymers, or through pH adjustment, providing floc formation which facilitates microalgal biomass sedimentation 13 . According to Duan and Gregory 14 , this process is critically dependent on pH values.…”
Section: Introductionmentioning
confidence: 99%
“…The coagulation-flocculation process, followed by sedimentation, has been the most widely adopted method because it has been shown to be economically viable for large production volumes of biomass 11,12 . The coagulation-flocculation process can promote microalgal aggregation by the addition of coagulants (electrolytes), which can be metal salts, natural or synthetic polymers, or through pH adjustment, providing floc formation which facilitates microalgal biomass sedimentation 13 . According to Duan and Gregory 14 , this process is critically dependent on pH values.…”
Section: Introductionmentioning
confidence: 99%
“…biomass for up to 159.78% and 207.46%, respectively for M. oleifera seed powder and M. oleifera protein powder. The performance of M. oleifera seed powder was confirmed by Teixeira et al [4] which reported its performance in harvesting marine microalgae from cultivation medium with the removal efficiency of more than 90%. Nevertheless, other research involving the investigation on M. oleifera protein powder was still lacking.…”
Section: Flocculation Assaysmentioning
confidence: 73%
“…In Malaysia, M. oleifera, commonly known as kacang merunggai is available locally and inexpensive hence making them a viable alternative to chemical coagulant in water and wastewater treatment, which is also possible as bioflocculants in the microalgae biomass separation process and harvesting [4]. Bio-coagulant from M. oleifera was reported to have a high flocculation potential in water treatment, attaining 92 -97 % flocculation efficiency [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…As dosagens do coagulante natural Moringa oleifera Lam utilizadas nos ensaios foram adaptadas segundo dados citados na literatura, sendo de 0,05; 0,1; 0,2; 0,4; 0,5; 0,6; 0,8 e 1,0 g.L -1 (Teixeira et al, 2012).…”
Section: Processo De C/f/fadunclassified